Ocular and Adnexal Lymphoma - Singh, Arun D. (Essentials in Ophthalmology, 2014)
This book - a conjoint effort of ocular oncologists, general oncologists, and pathologists - is a comprehensive source of authoritative information on the subject of ocular and adnexal lymphoma. It covers all aspects, including clinical features, classification, epidemiology, diagnostic evaluation, biopsy techniques, histology and molecular pathology, staging procedures, and treatment methods. Detailed information is provided on primary vitreoretinal and adnexal lymphomas and chapters are also included on rare variants such as T cell lymphoma and reactive lymphoid hyperplasia of the ocular adnexa. The emphasis throughout is on easy readability, and the layout ensures rapid retrieval of information. In order to convey fundamental concepts, numerous tables, clinical photographs, histopathologic microphotographs, and imaging studies (fluorescein and indocyanine angiograms, ultrasonograms, CT scans, and MR images) are included.